Respuesta :
Step-1 : Multiply the coefficient of the first term by the constant 3 • 4 = 12
Step-2 : Find two factors of 12 whose sum equals the coefficient of the middle term, which is 13 .
-12 + -1 = -13
-6 + -2 = -8
-4 + -3 = -7
-3 + -4 = -7
-2 + -6 = -8
-1 + -12 = -13
1 + 12 = 13
Step-2 : Find two factors of 12 whose sum equals the coefficient of the middle term, which is 13 .
-12 + -1 = -13
-6 + -2 = -8
-4 + -3 = -7
-3 + -4 = -7
-2 + -6 = -8
-1 + -12 = -13
1 + 12 = 13
Now, ASSUMING that you mean 3x^2+13x+4 for factors, your answer will be
(3x+1) (x+4)
If you meant 3x2+13x+4 then your answer will be
3x^2+17 ( ^ meaning squared)